Estrogen Signaling and the DNA Damage Response in Hormone Dependent Breast Cancers - Caldon, C. Elizabeth (Frontiers in Oncology, 2014)
Estrogen is necessary for the normal growth and development of breast tissue, but high levels of estrogen are a major risk factor for breast cancer. One mechanism by which estrogen could contribute to breast cancer is via the induction of DNA damage. This perspective discusses the mechanisms by which estrogen alters the DNA damage response (DDR) and DNA repair through the regulation of key effector proteins including ATM, ATR, CHK1, BRCA1 and p53 and the feedback on estrogen receptor signalling from these proteins. We put forward the hypothesis that estrogen receptor signalling converges to suppress effective DNA repair and apoptosis in favour of proliferation. This is important in hormone-dependent breast cancer as it will affect processing of estrogen-induced DNA damage, as well as other genotoxic insults. DDR and DNA repair proteins are frequently mutated or altered in estrogen responsive breast cancer which will further change the processing of DNA damage. Finally the action of estrogen signalling on DNA damage is also relevant to the therapeutic setting as the suppression of a DNA damage response by estrogen has the potential to alter the response of cancers to anti-hormone treatment or chemotherapy that induces DNA damage.